Using a hybrid algorithm and active RFID to construct a seamless infant rooming-in tracking mechanism. (2015) - Hung, Lun-Ping
Due to the rapid development of sensor and wireless equipment that integrates with information technology to construct intelligent mechanism, the quality of the clinical care of newborn babies has improved. To raise the success rate of requesting rooming-in care for newborn babies, baby-friendly hospitals should prevent the mistake of identifying newborns and assure the safety of newborn babies. This paper proposes a mechanism that includes a hybrid algorithm combining Location Fingerprint and K-nearest neighbour (KNN) algorithm and active radiofrequency identification technology using received signal strength indication transmission method to build a safer rooming-in environment. This mechanism can effectively avoid the situation, such as a stolen or switched baby, and be up to the standard certified by baby-friendly hospital initiative. The nursing department can easily arrange routine nursing works and increase nursing quality. The hospitals benefit from using the system with increased ratio of requesting rooming-in care.